Facts about the short story Imra'ah Galabat Al-Syaithan by Taufiq Al-Hakim: A Structuralist Study by Robert Stanton - Razaq, Elsa Naurah (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze the narrative structure of the short story Imra'ah Galabat al-Syaitha̅n by Taufiq Al-Hakim using Robert Stanton’s structuralist theory. This short story was selected because it contains strong moral and social values, particularly regarding the power of reason and the steadfastness of a woman’s heart in facing the devil’s temptations, which represent the struggle between good and evil.This study employs a qualitative descriptive method with a structural approach. Primary data was obtained from the text of the short story Imra'ah Galabat al-Syaitha̅n, while secondary data was sourced from academic journals and other supporting references.The analysis reveals that the narrative elements in this short story consist of three main components. First, the female protagonist, portrayed as a steadfast, intelligent, and unwavering figure, and the demon, depicted as a cunning and manipulative antagonist. Second, a simple yet well structured plot progression, spanning from exposition to resolution. Third, the setting, time, and atmosphere that reinforce the dramatic and spiritual context of the storyBased on the analysis, it can be concluded that Robert Stanton’s structuralism theory is relevant for analyzing Arabic literature. The narrative elements in this short story are interconnected and form a cohesive whole, effectively conveying the moral message of good triumphing over evil to the reader.